2005
DOI: 10.1557/jmr.2005.0322
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Induced Structural Transformations on Polymorphous Silicon

Abstract: Polymorphous Si is a nanostructured form of hydrogenated amorphous Si that contains a small fraction of Si nanocrystals or clusters. Its thermally induced transformations such as relaxation, dehydrogenation, and crystallization have been studied by calorimetry and evolved gas analysis as a complementary technique. The observed behavior has been compared to that of conventional hydrogenated amorphous Si and amorphous Si nanoparticles. In the temperature range of our experiments (650-700°C), crystallization take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…In both traces of Figure , the center of the low-temperature exothermic transition is near 350 °C. Exothermic transitions at similar temperatures have been experimentally observed in hydrogenated amorphous silicon, , porous silicon, and polymorphous silicon . They were attributed to effects associated with hydrogen desorption.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In both traces of Figure , the center of the low-temperature exothermic transition is near 350 °C. Exothermic transitions at similar temperatures have been experimentally observed in hydrogenated amorphous silicon, , porous silicon, and polymorphous silicon . They were attributed to effects associated with hydrogen desorption.…”
Section: Discussionsupporting
confidence: 65%
“…Exothermic transitions at similar temperatures have been experimentally observed in hydrogenated amorphous silicon, 28,29 porous silicon, 24 and polymorphous silicon. 30 They were attributed to effects associated with hydrogen desorption. Molecular dynamics simulations of hydrogen-terminated silicon nanoparticles have also demonstrated that hydrogen evolves from silicon nanocrystal surfaces in the same temperature range.…”
Section: Discussionmentioning
confidence: 99%